Porcine epidemic diarrhea virus nsp14 inhibits NF-κB pathway activation by targeting the IKK complex and p65 - Shasha Li; Fan Yang; Caina Ma; Weijun Cao; Jinping Yang; Zhenxiang Zhao; Hong Tian; Zixiang Zhu; Haixue Zheng (BMC, 2021)
Abstract Coronaviruses (CoVs) are a group of related enveloped RNA viruses that have severe consequences in a wide variety of animals by causing respiratory, enteric or systemic diseases. Porcine epidemic diarrhea virus (PEDV) is an economically important CoV distributed worldwide that causes diarrhea in pigs. nsp14 is a nonstructural protein of PEDV that is involved in regulation of innate immunity and viral replication. However, the function and mechanism by which nsp14 modulates and manipulates host immune responses remain largely unknown. Here, we report that PEDV nsp14 is an NF-κB pathway antagonist. Overexpression PEDV nsp14 protein remarkably decreases SeV-, poly (I:C)- and TNF-α-induced NF-κB activation. Meanwhile, expression of proinflammatory cytokines is suppressed by nsp14. nsp14 inhibits the phosphorylation of IKKs by interacting with IKKs and p65. Furthermore, nsp14 suppresses TNF-α-induced phosphorylation and nuclear import of p65. Overexpression nsp14 considerably increases PEDV replication. These results suggest a novel mechanism employed by PEDV to suppress the host antiviral response, providing insights that can guide the development of antivirals against CoVs.